Factors Affecting the Action of Mothers to Massage in Infants at BPM Talitha In 2021 - Rina Hanum; Mey Elisa Safitri (International Journal of Cultural and Social Science, 2021)
Data from BPM Talitha that the number of mothers who have babies 0-12 months as many as 32 people. The number of babies born with low birth weight (LBW) has increased over the last 2 years. In 2014 the number of babies born with underweight was 7 people, while in 2015 it increased to 10 people, and some babies were rarely given baby massage since birth. The purpose of this study was to determine the factors that influence mothers to massage their babies. This type of research is an analytic survey with a cross sectional approach. The research was conducted at BPM Talitha, Deli Serdang Regency. The total population is 32 people, and all of them are used as samples. Data were analyzed by univariate and bivariate using Chi-Square test. The results showed that the mother's knowledge was sufficient for 15 (46.9%) respondents, 18 (62.5%) negative attitudes, 20 (59.4%) respondents lacked support from health workers. The factors that influence mothers to massage their babies at BPM Talitha are knowledge (p = 0.005), attitude (p = 0.003), support from health workers (p = 0.004). It is hoped that health workers will provide health education about the benefits and advantages of doing baby massage to mothers at BPM Talitha so that mothers' knowledge and attitudes become more positive.